2011
DOI: 10.1007/s00417-011-1646-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the severity of vision loss on vision-specific functioning in a German outpatient population — an observational study

Abstract: Using a psychometrically valid German-translated VF-14, even mild vision impairment was independently associated with poor visual functioning. These findings reinforce the importance of early preventative and rehabilitative efforts to prevent longitudinal deterioration in vision loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
6
2
3
Order By: Relevance
“…This differs from findings from developed countries where even mild VI has been found to be associated with poor vision-specific functioning and VRQoL. 38,39 This finding reflects the present protocol for cataract surgery referral in developing or transitional countries such as India, where priority is given to patients with at least moderate to severe VI. 40 The decision of patients to accept recom-mended cataract surgery is based on a complex set of factors, 41,42 including individually perceived levels of vision-specific functioning and quality of life, 43 which may not be affected until VI has progressed to the more severe stages.…”
Section: Discussioncontrasting
confidence: 59%
“…This differs from findings from developed countries where even mild VI has been found to be associated with poor vision-specific functioning and VRQoL. 38,39 This finding reflects the present protocol for cataract surgery referral in developing or transitional countries such as India, where priority is given to patients with at least moderate to severe VI. 40 The decision of patients to accept recom-mended cataract surgery is based on a complex set of factors, 41,42 including individually perceived levels of vision-specific functioning and quality of life, 43 which may not be affected until VI has progressed to the more severe stages.…”
Section: Discussioncontrasting
confidence: 59%
“…Detailed information regarding the Rasch results and the impact of visual impairment and ocular conditions on visual functioning as measured with the VF-14 has been reported elsewhere. 21 Both measures (i.e., the LLQ-23 and the VF-14) were highly correlated (Pearson correlation coefficient 0.701, P Ͻ 0.001).…”
Section: Relationship Between Vision Impairment and Vision-related Qumentioning
confidence: 97%
“…It has been well established that poor vision is associated with depression. 142225 This may be exacerbated in developing countries where the visually impaired may be seen as a socioeconomic burden and there are fewer resources to aid them. Previous studies have suggested an increase in impact of visual disability in developing countries compared with developed countries.…”
Section: Discussionmentioning
confidence: 99%